lithogeochemistry characterization and correlation analysis of superunits intrusive Yarabamba and Challaviento in southern Peru - Rivera, Hugo (2013)
The constituents of superunits Yarabamba and Challaviento in southern Peru, according to its composition of major elements, minor and trace and graphing various intrusive rocks geochemical diagrams show that both superunits have a degree of evolution by fractional crystallization They are sub-alkaline nature and high K calc-alkaline seriesThe rocks are both superunits metaluminous nature. The contents of Sr and Rb indicate a strong assimilation and differentiation of magmas. The enrichment of LILE (<100) elements and an impoverishment of less HFSE elements 10, negative anomalies of Nb and positive anomalies of Th, Ce, indicate that both groups are related to intrusive tectonic plate subduction context. The chemical content of the SuperDrive Yarabamba and Challaviento Ce / and Ga / Al and Y, Y + Nb and Rb and Nb are due to contamination during crustal thickening during the Cretaceous-Neogene tectonic setting and is the Volcanic Arc granitoids (GAV).